Narrower clinical margin in high or very high‐risk squamous cell carcinoma: a retrospective, multicenter study of 1, 000 patients. (4th August 2022) - Baba, Natsuki; Kato, Hiroshi; Nakamura, Motoki; Matsushita, Shigeto; Aoki, Megumi; Fujimoto, Noriki; Kato, Takeshi; Iino, Shiro; Saito, Shintaro; Yasuda, Masahito; Asai, Jun; Ishikawa, Masashi; et al.
Summary: Background and objectives: In cutaneous squamous cell carcinoma (cSCC), adherence to guideline‐recommended fixed surgical margins is often difficult, and narrower margins are preferable. This study aimed to evaluate relapse and disease‐specific death with narrower margins for high or very high‐risk cSCC. Patients/Methods: We retrospectively investigated high or very high‐risk cSCC patients who underwent tumor excision. Patients were divided into guideline‐recommended standard margin group (SMG) and narrower‐margin group (NMG). Co‐primary outcomes were local relapse, SCC relapse, and SCC death. Cumulative incidence function (CIF) was used to describe SCC death probability and competing risk mortality. Gray's test was used to compare differences in CIF between the groups. Results: In total, 1, 000 patients with cSCC (high‐risk, 570; very high‐risk, 430) were included. In the high‐risk cohort, there were no significant differences in incomplete excision rate (IER) between SMG and NMG (2.6 % vs. 3.0 %, P > 0.99). However, in the very high‐risk cohort, IER in SMG was significantly lower than in NMG (8.9 % vs. 16.2 %, P = 0.03). No significant differences were observed between SMG and NMG for local relapse (high‐risk, P = 0.56; very high‐risk, P = 0.70), SCC relapse (high‐risk, P = 0.30; very high‐risk, P = 0.47), and SCC death (high‐risk, P = 0.23; very high‐risk, P = 0.83). Conclusions: Surgical margin size has limited impact on margin control, relapse, and disease‐specific death in high‐risk cSCC.